Bioactive phenolic compounds : production and extraction by solid-state fermentation. A review - Martins, Silvia (2011)
Interest in the development of bioprocesses for the production or extraction of bioactive compounds from natural sources has increased in recent years due to the potential applications of these compounds in food, chemical, and pharmaceutical industries. In this context, solid-state fermentation (SSF) has received great attention because this bioprocess has potential to successfully convert inexpensive agro-industrial residues, as well as plants, in a great variety of valuable compounds, including bioactive phenolic compounds. The aim of this review, after presenting general aspects about bioactive compounds and SSF systems, is to focus on the production and extraction of bioactive phenolic compounds from natural sources by SSF. The characteristics of SSF systems and variables that affect the product formation by this process, as well as the variety of substrates and microorganisms that can be used in SSF for the production of bioactive phenolic compounds are reviewed and discussed.